The tigecycline resistance mechanisms in Gram-negative bacilli - Wang, Zhiren; Li, Henan (Frontiers in Cellular and Infection Microbiology, 2024)
Tigecycline, hailed as a pivotal agent in combating multidrug-resistant bacterial infections, confronts obstacles posed by the emergence of resistance mechanisms in Gram-negative bacilli. This study explores the complex mechanisms of tigecycline resistance in Gram-negative bacilli, with a particular focus on the role of efflux pumps and drug modification in resistance. By summarizing these mechanisms, our objective is to provide a comprehensive understanding of tigecycline resistance in Gram-negative bacilli, thereby illuminating the evolving landscape of antimicrobial resistance. This review contributes to the elucidation of current existing tigecycline resistance mechanisms and provides insights into the development of effective strategies to manage the control of antimicrobial resistance in the clinical setting, as well as potential new targets for the treatment of tigecycline-resistant bacterial infections.